Fluctuations of Temperature and Thermal Energy in the Place of Double Diffusion Structures in the Strait of Hormuz - Mostafa Solgi; Mahdi Mohammad-Mahdizadeh; Abbas Ali Ali Akbari Bidokhti; Smaeyl Hassanzadeh (Nīvār)
Double Diffusion Convection (DD) structures, in two types of Salt-Fingering (SF) and Diffusive Convection (DC), occur due to vertical temperature and salinity gradients with different diffusion coefficients. And thermohaline circulation in the Strait of Hormuz often causes the formation of SF on the surface and in the northern or middle parts of the strait and DC structure in the depth and southern parts of the Strait of Hormuz. In this study, the formation of DD structures and their role in temperature changes and thermal energy of water in the Strait of Hormuz have been investigated. This effect depends on the formation conditions of diffusion structures and the average temperature and thermal energy of the water mass. Due to the fluctuations resulting from the DD structures in the hot days of the year, a 2-5% change in the temperature and thermal energy of water is observed. So that the maximum changes up to 5% (change in energy) occur in the southern parts of the strait. The heat exchange during the DC process is higher than that of SF (more than 10 times). However, the thermal energy is minimal at the place of the cold mass and strong convection, and the DC structure is weakened due to the increased energy exchange with the environment,. This heat exchange causes the internal energy of water to decrease by about 250 J. While during the growth of SF, the temperature and thermal energy of the environment (on a small scale) increases.